Physical characteristics of Kosali breed of cattle in its native tract - JAIN, ASIT; BARWA, DEEPTI K; SINGH, MOHAN; MUKHERJEE, KISHORE; JAIN, TRIPTI; TANTIA, M S; RAJA, K N; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2018)
Kosali, the first breed of cattle from Chhattisgarh, was registered as 36th breed. Characterization is essential to guide decision-making in livestock development and breeding programmes. Hence, a survey was carried out to characterize the Kosali breed of cattle in Central Plain Region of Chhattisgarh state. The coat colour of most animals was red followed by white and black. Mostly muzzles, tail switch, eyelashes, and hooves were black in colour. Body size, hump, dewlap, naval flap, penis sheath flap, udder and teats were small in size. Horns were stumpy, small and slightly inward and ears were horizontal. The estimated average live weight of adult female and male were 168.7±2.82 and 212.5±3.8 kg, respectively. The mean linear measurements of female vs male Kosali cattle were height at wither (99.79±2.76 vs 103.4±2.11 cm), body length (96.56±1.87 vs 99.89±2.32 cm) and chest girth (119.98±1.98 vs 137.12±2.8 cm). Kosali cattle are smaller in size and are well adapted to the existing agroclimatic conditions of the region. Appropriate breeding strategies and conservation models should be designed for overall improvement of this breed.